2020
DOI: 10.1021/acs.jpclett.0c02327
|View full text |Cite
|
Sign up to set email alerts
|

Phosphorylation-Dependent Conformations of the Disordered Carboxyl-Terminus Domain in the Epidermal Growth Factor Receptor

Abstract: The epidermal growth factor receptor (EGFR), a receptor tyrosine kinase, regulates basic cellular functions and is a major target for anticancer therapeutics. The carboxylterminus domain is a disordered region of EGFR that contains the tyrosine residues, which undergo autophosphorylation followed by docking of signaling proteins. Local phosphorylationdependent secondary structure has been identified and is thought to be associated with the signaling cascade. Deciphering and distinguishing the overall conformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 80 publications
0
21
0
Order By: Relevance
“…The transient dynamics of salt bridge formation and deformation are thus relayed to the surrounding liquid via changes in water's interfacial polarization response. These changes may play a role in modulating the water-mediated effects that drive conformational changes (38)(39)(40) or the nascent stages of protein-protein (41) or protein-ligand binding (2).…”
Section: Role Of Water-water Interactions In the Nonlinear Response Of Interfacial Water When Strong Surface-water In-mentioning
confidence: 99%
“…The transient dynamics of salt bridge formation and deformation are thus relayed to the surrounding liquid via changes in water's interfacial polarization response. These changes may play a role in modulating the water-mediated effects that drive conformational changes (38)(39)(40) or the nascent stages of protein-protein (41) or protein-ligand binding (2).…”
Section: Role Of Water-water Interactions In the Nonlinear Response Of Interfacial Water When Strong Surface-water In-mentioning
confidence: 99%
“…Moreover, full description of the tail conformation should include phosphorylated states, which are, to our knowledge, not well described in terms of multiplicity and heterogeneity, and difficult to reproduce. The phosphorylated states structurally described so far are therefore either phosphomimetics [28], synthetic monophosphorylations [29], or in vitro autophosphorylation products which were shown to have, on average, one phosphate per tail, which may not be physiologically relevant [34,35].…”
Section: Structural Description Outside Of Regions Interacting With the Kinasementioning
confidence: 99%
“…IDPs are therefore ideal candidates to participate in signal transduction [24,25]. Recent studies have explicitly confirmed that CT-ErbBs are disordered [26][27][28][29][30]. For a long time, the conformational properties of these tails were not included in studies, and they were treated as mere "strings" attaching the tyrosine phosphorylation sites to the rest of the receptor.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The maximum entropy optimization algorithm was developed for parameterizing transferable IDP force fields using biasing energies derived from experimental constraints. 44,45 Energy gap maximization, on the other hand, has been a successful strategy for deriving force fields of folded proteins. [46][47][48][49] The resulting force field, MOFF, indeed provides a more balanced set of interactions that can predict the radii of gyration of both ordered and disordered proteins.…”
Section: Introductionmentioning
confidence: 99%